Inpatient resource use and costs associated with switching from oral antipsychotics to aripiprazole once-monthly for the treatment of schizophrenia - Michele Wilson; Benjamin Gutierrez; Steve J Offord; Christopher M Blanchette; Anna Eramo; Stephanie Earnshaw; Siddhesh A Kamat (BioExcel Publishing Ltd, 2016)
Background: Schizophrenia is associated with high direct healthcare costs due to progression of disease and frequent occurrence of relapses. Aripiprazole once-monthly (AOM) has been shown to reduce total psychiatric hospitalizations among patients who switched from oral standard of care (SOC) therapy to AOM in a multicenter, open-label, mirror-image study of patients with schizophrenia. Because of the increasing need to improve patient outcomes while containing costs, it is important to understand the impact of AOM treatment initiation on medical costs associated with psychiatric hospitalizations and antipsychotic pharmacy costs. Methods: In the current study, an economic model was developed using data from the AOM mirror-image study to evaluate the psychiatric hospitalization-related medical costs and antipsychotic pharmacy costs during a 6-month period before (retrospective period) and after (prospective period) the AOM treatment initiation. The economic model evaluated cost-saving potential of AOM among all patients (n=433) as well as a subset of patients with ≥1 prior hospitalization (n=165) who switched from oral SOC to AOM. Unit cost data were obtained from publicly available sources. Results: Both hospitalizations and hospital days were reduced following a switch from oral SOC to AOM. As a result, psychiatric hospitalization-related costs were lower during the prospective period when compared with the retrospective period. Furthermore, the increase in antipsychotic pharmacy costs due to switching from oral SOC to AOM was offset by a reduction in psychiatric hospitalization-related medical costs. Per-patient costs were reduced by $1,046 (USD) in the overall population and by $20,353 in a subset of patients who had at least 1 psychiatric hospitalization during the retrospective period. Results were most sensitive to changes in hospitalization costs. Conclusions: AOM is associated with reducing the risk of relapse among patients with schizophrenia. The increase in antipsychotic pharmacy costs due to switching from oral SOC to AOM was offset by a reduction in costs associated with psychiatric hospitalizations, thereby presenting a cost-saving opportunity for health plans.